SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE AHP UNTUK PEMILIHAN SUPPLIER BAHAN BAKU (STUDI KASUS: PT AKRILIK KURNIA KENCANA) - Lisda Amalia; Fitri Yanti (CV. Multi Kreasi Media, 2024)
In facing the challenges of globalization, selecting the right raw material supplier is a key factor in supporting the performance of PT Akrilik Kurnia Kencana. Companies face difficulties in choosing reliable suppliers, which risks affecting product quality and production costs. As a solution, a Decision Support System (DSS) was implemented using the Analytical Hierarchy Process (AHP) method, which allows objective evaluation of various criteria. It is hoped that the implementation of this system can increase efficiency and effectiveness in supplier selection, as well as support the company's strategic decisions. Overall, AHP can help companies make more precise decisions, improve performance, and utilize information technology in decision making.